1977
DOI: 10.1029/ja082i032p05112
|View full text |Cite
|
Sign up to set email alerts
|

Two types of magnetospheric ELF chorus and their substorm dependences

Abstract: Extremely low frequency (10-1500 Hz) magnetospheric chorus has been analyzed to investigate a possible dependence on substorms. Care was taken to separate spatial effects from temporal effects by analyzing an entire year of data acquired by the Ogo 5 search coil magnetometer. A major finding of the study of spatial dependences is that chorus occurs principally in two magnetic latitude regions. Equatorial chorus is detected near the equator, and high-latitude chorus is found at magnetic latitudes above 15 ø. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
498
2
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 408 publications
(536 citation statements)
references
References 50 publications
34
498
2
1
Order By: Relevance
“…Though the above estimations are based upon a number of simplified models and thus approximate only, they guide us to tentatively suggest that the ECH be a more promising candidate for higher L shell PsAs as in our event. However, one should be noted that the whistle-mode chorus may well have an off-equatorial source [Tsurutani and Smith, 1977;Sigsbee et al, 2010] which could not be observed by THEMIS satellites. We thus may not entirely exclude, from both theoretical and observational viewpoints, the possible existence of the chorus waves as well as their potential role in generating the observed PsAs in our event.…”
Section: Discussionmentioning
confidence: 97%
“…Though the above estimations are based upon a number of simplified models and thus approximate only, they guide us to tentatively suggest that the ECH be a more promising candidate for higher L shell PsAs as in our event. However, one should be noted that the whistle-mode chorus may well have an off-equatorial source [Tsurutani and Smith, 1977;Sigsbee et al, 2010] which could not be observed by THEMIS satellites. We thus may not entirely exclude, from both theoretical and observational viewpoints, the possible existence of the chorus waves as well as their potential role in generating the observed PsAs in our event.…”
Section: Discussionmentioning
confidence: 97%
“…Twelve orbits, during which nontraditional configurations were deployed for testing purposes, were also excluded from the analyses. Tsurutani and Smith [1977] showed that the chorus emissions could be divided into two categories depending on magnetic latitude. The same scheme and notation are adopted here with equatorial and high-latitude chorus being defined as chorus observed within and beyond 15 ø of the magnetic equator, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Nightside chorus is strongest inside L = 8, and is also confined to latitudes below 15 • , due to strong Landau damping of oblique waves during their propagation towards higher latitude from the equatorial source region ). In contrast, dayside chorus is found over a broad range of latitudes, is most intense in the outer (L ≈ 8) magnetosphere, and shows less dependence on geomagnetic activity (Tsurutani and Smith 1977;. The wave normal distribution of chorus is required to accurately evaluate resonant electron energies and quantify the associated rates of scattering ).…”
Section: Fig 2 Spectrogram Of Waves Observed On Combined Release Andmentioning
confidence: 99%